Are school difficulties an early sign for mental disorder diagnosis and suicide prevention? A comparative study of individuals who died by suicide and control group - Ligier, Fabienne (Child Adolesc Psychiatry Ment Health, 2020)
BACKGROUND: Suicide is the third leading cause of death worldwide among youth aged 10- to 19, and mental disorders are often associated in the etiology of suicidal behavior. Mental disorders are often under-diagnosed and under-treated in young people, a situation likely to increase the severity of the disorder and suicide risk. Presence of school difficulties may, in some cases, be a consequence of mental disorder, and theses difficulties are observable. Therefore, early detection and early intervention of school difficulties may alleviate the development of mental disorders and suicide vulnerability. The aim of this study is to understand the link between school difficulties and suicide risk. METHODS: We used the data bank gathered by the McGill Group on Suicide Studies over the past two decades through interviews with the relatives of individuals who died by suicide and with individuals from the community as a control group. We included data on common sociodemographic characteristics, life events and mental health characteristics identified before age 18, among individuals who died before the age of 35 or were interviewed before the age of 35. We identified 200 individuals who died by suicide and 97 living controls. We compared groups according to gender and characteristics. RESULTS: Within the total sample, 74% were male, 13% had met with academic failure, 18% had engaged in inappropriate behavior at school, and 18% presented combined school difficulties. Combined school difficulties (academic failure and inappropriate behavior) for both sexes and academic failure alone for males were associated with higher suicide risk before the age of 35. School difficulties generally began in early childhood and were linked to mental disorders/difficulties and substance abuse before age 18. CONCLUSIONS: This study underlines the importance for parents, teachers, and educators to identify children with school difficulties—academic failure and behavioral difficulties at school—as early as possible in order to be able to propose adapted interventions. Early identification and proper diagnosis may prevent chronicity of some disorders, accumulation of adverse events, and even suicide.